Radiolabeling of substance P with lutetium-177 and biodistribution study in rat pancreatic tumor xenografted nude mice - De araújo, E. B.; Pujatti, P. B.; Mengatti, J. (Cellular and Molecular Biology, 2010)
Pancreatic tumor (PT) is a neuroendocrine neoplasm that usually origin metastases in the respiratory and gastrointestinal tract. The presence of peptide receptors at the cell membrane of PT constitutes the basis of the clinical use of specific radiolabeled ligands for its diagnosis and targeted therapy. Substance P (SP), an 11-amino acid peptide which has an important role in modulating pain transmission trough neurokinin type 1 (NK1r) and 2 receptors (NK2r), may play a role in the pathogenesis of PT, because approximately 10% of these tumors overexpress NK1r. The aim of the present work was to produce a pure and stable SP analog (DOTA-SP) radiolabeled with lutetium-177 (177Lu), and to evaluate its in vivo target to AR42J pancreatic tumor cells in Nude mice, in other to verify if SP can be used in this pancreatic tumor detection and treatment. Substance P was successfully labeled with high yield (>99%) at optimized conditions and kept stable for more than 72 hours at 2-8º C and 4 hours in human plasma. Biodistribution studies showed that SP excretion was mainly performed by renal pathway. In addition, 177Lu-DOTA-SP showed higher uptake by tumor than normal pancreas, indicating the presence of NK receptors in AR42J pancreatic tumor.